2021
DOI: 10.1155/2021/2520394
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition Based on EEG Using Generative Adversarial Nets and Convolutional Neural Network

Abstract: Emotion recognition plays an important role in the field of human-computer interaction (HCI). Automatic emotion recognition based on EEG is an important topic in brain-computer interface (BCI) applications. Currently, deep learning has been widely used in the field of EEG emotion recognition and has achieved remarkable results. However, due to the cost of data collection, most EEG datasets have only a small amount of EEG data, and the sample categories are unbalanced in these datasets. These problems will make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Te CNN has the advantages of local connectivity and shared weights and has the ability to mine and integrate the local information of matrix signals [21], so it is suitable for analyzing the spatial connection of each channel in 2D matrix signals in this paper. In recent years, some scholars have tried to use the CNN to analyze the internal spatial connections of EEG signals, but most of them combine shallow multidomain features of single channels, then merge these features into matrix signals as input, and fnally further mine spatial information from the merged features [22].…”
Section: Spatial Features Extracted By Cnnmentioning
confidence: 99%
“…Te CNN has the advantages of local connectivity and shared weights and has the ability to mine and integrate the local information of matrix signals [21], so it is suitable for analyzing the spatial connection of each channel in 2D matrix signals in this paper. In recent years, some scholars have tried to use the CNN to analyze the internal spatial connections of EEG signals, but most of them combine shallow multidomain features of single channels, then merge these features into matrix signals as input, and fnally further mine spatial information from the merged features [22].…”
Section: Spatial Features Extracted By Cnnmentioning
confidence: 99%
“…Very few articles have used tanh, linear and sigmoid function in the middle layers. But when the activation function was changed to Leaky ReLU, there was a signi cant improvement in the performance of accuracy [19]. It was also inferred that softmax function was mostly used in the output layer of the model for multiclass classi cation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The accuracy was estimated as 90%for arousal and 89% for valence. Pan et al[19] have used Power spectral density-Generative adversarial network to overcome the imbalance between the samples. In the rst model network, they have used two ReLU function and one tanh function.…”
mentioning
confidence: 99%
“…To evaluate the performance of the proposed approach in a fair fashion, we further evaluated the performance of the proposed approach and the state-of-the-art algorithms (Shawky et al, 2018;Yang et al, 2018Yang et al, , 2019Xing et al, 2019;Shen et al, 2020;Pan and Zheng, 2021;Rudakov, 2021;Kan et al, 2022;Zhang et al, 2022) on the DEAP dataset (as shown in Table 5). Accordingly, we used the DEAP dataset during the training phase of the proposed approach in this stage.…”
Section: Comparison Experiments Between the State-of-the-arts And The...mentioning
confidence: 99%